Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1136/injuryprev-2019-043468
|View full text |Cite
|
Sign up to set email alerts
|

Planning injury prevention training for youth handball players: application of the generalisable six-step intervention development process

Abstract: BackgroundYouth handball players are vulnerable to injuries. Because there is no available injury prevention training specifically developed for youth handball players targeting both upper and lower limbs or incorporating psychological aspects of injury, we undertook the ‘Implementing injury Prevention training ROutines in TEams and Clubs in youth Team handball (I-PROTECT)’ project. We used an ecological participatory design incorporating the perspectives of multiple stakeholders (health beneficiaries, program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…A possible explanation for these different views is that not all coaches used the program as intended (i.e., to integrate some of the exercises into warm-up and some into handball skills training) but put the exercises in one block separate from other parts of practice, which could be experienced by the players as “it takes too long of a time from our practice” (statement of a female player). It emerged from earlier steps in developing the I-PROTECT GO pilot program [ 20 , 23 ] and was recently confirmed by Møller and colleagues [ 12 ] that injury prevention training needs to be integrated into regular practice. A take-away based on this result is that coaches need to be better educated about how to optimally integrate injury prevention training into their regular routine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A possible explanation for these different views is that not all coaches used the program as intended (i.e., to integrate some of the exercises into warm-up and some into handball skills training) but put the exercises in one block separate from other parts of practice, which could be experienced by the players as “it takes too long of a time from our practice” (statement of a female player). It emerged from earlier steps in developing the I-PROTECT GO pilot program [ 20 , 23 ] and was recently confirmed by Møller and colleagues [ 12 ] that injury prevention training needs to be integrated into regular practice. A take-away based on this result is that coaches need to be better educated about how to optimally integrate injury prevention training into their regular routine.…”
Section: Discussionmentioning
confidence: 99%
“…Although the importance of involving end-users in developing and evaluating injury prevention programs has been promoted [ 10 , 23 , 29 , 30 ], injury prevention training programs have frequently been developed by researchers with little [ 9 , 31 ] or no involvement of end-users [ 32 , 33 , 34 ]. One recent exception is Bruder et al [ 22 ], who involved experts and end-users when developing a context-specific program for female Australian Football players.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, the ‘Implementing injury Prevention training ROutines in TEams and Clubs in youth Team handball (I-PROTECT)’ project was initiated through dialogue between end-users and researchers in 2015 with the overall goal to make injury prevention training part of regular handball practice in youth handball through a series of studies. While available injury prevention training for handball players commonly has a researcher-perspective focusing on evidence-based content and poorly described end-user involvement,17–19 I-PROTECT has an ecological participatory design incorporating the perspectives of multiple stakeholders (health beneficiaries, programme deliverers, policymakers) throughout the project 7 22. The first I-PROTECT study identified the facilitators among stakeholders at multiple levels that could help embed injury prevention training in regular training routines 7.…”
Section: Introductionmentioning
confidence: 99%